(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Hapsari L, Damaiyani J, Yulistyarini T, Auliya I, Gusmiati LH, Zaro RM. 2022. Characterization, potential and conservation of Pisang Kates (Musa cv. ABB), a unique local banana cultivar from Pasuruan, East Java, Indonesia. Biodiversitas 23: 3521-3532. Characterization of local banana (Musa spp.) germplasm is fundamental for identification and provides information on traits that support their sustainable conservation and optimum utilization. This study aims to characterize and discuss the potential and conservation of Pisang Kates,a local cultivar originatingfrom Tutur, Pasuruan, East Java, Indonesia. The observed characteristics include morphology, molecular, agronomy and yield performance, leaf anatomy and stomata, pollen morphology and viability, fruit total soluble solids and nutrients. Results showed that Pisang Kates hasa unique fruit shape ovoid to globose, weight of40-150 g, appear solitary and randomly attached directly to peduncle, like papaya. It was molecularly by Internal Transcribed Spacer barcode confirmed as ABB genotype. It is tolerant to drought and banana bunchy top virus, but susceptible to wilts. Leaf anatomy has three palisades and isodiametric polygonal epidermals. Leaf stomata is amphistomatic, tetracytic on adaxial,and paracytic on abaxial. Pollen unit is monad, very large, subspheroidal, monocolpate aperture, granulum ornamentation, and low viability. Fruit moderately sweet with nutrient contents equal to dessert banana. Pisang Kates has potential as one serving consumer size fruit, ornamental fruit plant, female parent for breeding,and pioneer plant for rehabilitation programs. Both ex-situ and on-farm conservation strategies of this valuable local banana genetic resource are encouraged.